Improvement of stability of insecticidal proteins from against UV-irradiation by adsorption on sepiolite - Xueyong Zhou; Hang Li; Yanmei Liu; Jianchao Hao; Huifen Liu; Xianzhi Lu (Adsorption Science & Technology)
The adsorption characteristics of protoxin and toxin from Bacillus thuringiensis by sepiolite were studied. The kinetic results showed that the protoxin and toxin could be adsorbed by sepiolite rapidly, and the equilibrium was reached within 1 h. The adsorption isotherms of both proteins followed Langmuir equation (R 2 >0.98) and the curves belonged to L type. The adsorption capacity, adsorption rate and the insecticidal activity of toxin were higher than those of protoxin. The results of ultraviolet irradiation showed that sepiolite could protect the toxin from ultraviolet irradiation damage, but it accelerated the damage of protoxin. Therefore, the toxin is suitable for preparing long-term formulations of B. thuringiensis using the carrier of sepiolite. The results of Fourier transform infrared, X-ray diffraction, and scanning electron microscopy indicated that toxin did not influence the structure of sepiolite and the adsorption of toxin only on the surface of sepiolite. The adsorption of toxin by sepiolite was enhanced by metal ions in the range of concentration from 0 to 4.0 mmol L −1 , and the enhancement extent of metal ions on the adsorption of toxin was in the order: Ca 2+ >Mg 2+ >K + >Na + . The higher the loading of toxin per mass sepiolite, the lower the 50% of the larvae of sepiolite–toxin complex. The zeta potential of sepiolite suspension increased with the addition of metal ions, indicating that the driving forces of the adsorption of toxin to negatively charged sepiolite was electrostatic interaction.